2022
DOI: 10.3389/fonc.2022.1029491
|View full text |Cite
|
Sign up to set email alerts
|

Coffee reduces the risk of hepatocellular carcinoma probably through inhibition of NLRP3 inflammasome activation by caffeine

Abstract: Fan FS (2022) Coffee reduces the risk of hepatocellular carcinoma probably through inhibition of NLRP3 inflammasome activation by caffeine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Conversely, it is important to note that both coffee and caffeic acid, a bioactive compound found in various herbs, vegetables, and fruits, hold promising anticancer potential. As an example, coffee consumption has been associated with a reduced risk of hepatocellular carcinoma [ 13 ]. Similarly, caffeic acid exhibits antitumor actions by exerting pro-oxidant and antioxidant properties, inhibiting reactive oxygen species formation, and suppressing angiogenesis and matrix metalloproteinases, suggesting its therapeutic implications for cancer treatment and prevention [ 14 ].…”
Section: Influence Of Dietary Factors On Bladder Cancer Riskmentioning
confidence: 99%
“…Conversely, it is important to note that both coffee and caffeic acid, a bioactive compound found in various herbs, vegetables, and fruits, hold promising anticancer potential. As an example, coffee consumption has been associated with a reduced risk of hepatocellular carcinoma [ 13 ]. Similarly, caffeic acid exhibits antitumor actions by exerting pro-oxidant and antioxidant properties, inhibiting reactive oxygen species formation, and suppressing angiogenesis and matrix metalloproteinases, suggesting its therapeutic implications for cancer treatment and prevention [ 14 ].…”
Section: Influence Of Dietary Factors On Bladder Cancer Riskmentioning
confidence: 99%
“…Espresso coffee is among the best known beverages worldwide, and drinking espresso has become a habit in many countries due to its pleasant taste. For many years, coffee consumption was associated with health risks; however, recent studies showed that when consumed in moderation, this soft drink could have beneficial effects on human health thanks to its biological properties. , The analysis and review of observational studies present in the literature suggest that consuming coffee could be advantageous against a number of chronic diseases, including some cancers (liver, colorectal, endometrial, and prostate), metabolic diseases (type-2 diabetes and metabolic syndrome), and neurological disorders (Parkinson′s disease, Alzheimer′s disease, and depression) . In particular, numerous studies report that moderate and, sometimes, even high coffee consumption exerts a neuroprotective action against two of the most common neurodegenerative diseases, i.e., Parkinson′s and Alzheimer′s. Many coffee compounds display beneficial properties in alleviating disease symptoms, for instance by reducing cognitive and memory impairment, as antioxidants, or by preventing amyloid formation and neurotoxicity .…”
Section: Introductionmentioning
confidence: 99%